The truth about Ryan - John, Laurie; Pascal, Francine (New York : Bantam, 1997)
Ryan Taylor is losing his battle against alcohol and Elizabeth finds herself unable to help him. Meanwhile, Jessica has her heart set on finding a new boyfriend.
Young Adult.
Young Adult
Keywords: Alcoholics -- Fiction; Lifeguards -- Fiction; Man-woman relationships -- Fiction; Alcoholics -- Fiction; Lifeguards -- Fiction; Love stories